RESPON PERTUMBUHAN DAN PRODUKSI TANAMAN TOMAT (Solanum lycopersicum) TERHADAP PEMBERIAN NPK 16-16-16 DENGAN MODIFIKASI MEDIA TANAM KOMPOS KULIT KAKAO - Annisa Rahmana Resyad; Irwan Agusnu Putra; Dedi Kurniawan; Yunida Berliana (Prodi. Agroteknologi dan Perkebunan, Universitas Tjut Nyak Dhien, 2023)
Introduction: Tomato plants (Solanum lycopersicum) are vegetable in vitamins A, B, C. In the cultivation of tomato plants, it is necessary to maximize the growth and production of tomato plants, the application of NPK which can add nutrients to plants. Then, cocoa husk compost which provides nutrients, improves soil structure. Methods: This research was carried out in November 2022 - February 2023 at Jln. Yos Sudarso Dusun III Kec. Binjai, Kab. Langkat. North Sumatra. The study used a 2-factor factorial randomized block design (RAKF), the first factor was NPK 16-16-16, N0 (10 g/plant), N1 (20 g/plant), N2 (20 g/plant), N3 (30 g/plant). the second factor was the modification of the planting medium for cocoa shell compost, M0 (Top soil), M1 (Top soil + Cocoa Hull Compost 1:½), M2 (Top soil + Cocoa Hull Compost 1:1), M3 (Top soil + Cocoa Hull Compost 1:1½). Parameters observed were plant height, soil water content, fruit weight planted, and total harvest weight. Results: The results showed that the npk 16-16-16 treatment had a significant effect on plant height growth, fruit planting weight, total harvest weight, the best treatment was N3. modification of the planting medium of cocoa shell compost had a significant effect on fruit weight per plant, soil water content, total harvest weight, the best treatment was M3. The interaction of NPK 16-16-16 and modification of the planting medium of cocoa shell compost had no significant effect on all parameters, the best treatment was N2M1. Keywords: Tomato, NPK, Cocoa Husk Compost.